Mai Cafe / Muhammad Shamil Haziq Salimen ...[et al.] - Salimen, Muhammad Shamil Haziq; Anuar, Muhammad Ikhwan; Isnin, Muhammad Faiszam; Kamaruzaman, Abdullah Fayyadh; Amir Azlan, Amirul Abid (2022)
Our business is named Mai Cafe. Mai Cafe serves beverages such as coffees and teas. We also served mouth-watering baked goods and snacks. The location of Johor Bahru illustrates that most of our customers are middle class people who always consume the goods at a reasonable price. The workers and students who work and study there are our major objective, as our cafe is very close to some institutions and the workplace. Other than that, there are a few shopping complexes nearer. We are the only café around the area that is the big attraction to our customers, and our shop is unique. With a reasonable price our marketing strategy concentrates more on the quality. By using social media we also promote more over our business and placed a very huge billboard at our cafe. We hope that many people there will know our cafe by doing this. We want our cafe popular, because it has its own specialty and it's got some space for our Instagram, Facebook and other applications to capture shots.